Persuasiveness of online product recommendations : the roles of warranting theory and credibility - Lew, Zi Jian (2017)
When people make decisions, they want to know if the information they obtain online comes from authentic sources. Online judgments of a communicator’s authenticity involve making evaluations on at least three criteria: the warranting value of information, the communicator’s credibility, and the credibility of those who provide information about the communicator. This study articulates two theoretically novel aspects of warranting theory: meta-warranting (communicators’ tendency to be more truthful when an observer can corroborate their claims than when observers cannot) and meta-meta-warranting (an observer’s perception that a communicator is truthful when the communicator provides the observer with the potential to corroborate information). Through an experiment set in a crowdfunding context, support was found for the meta-meta-warranting prediction that if observers are afforded the potential to corroborate information about a target communicator, they believe that the communicator is more authentic than if they are not afforded the potential to corroborate.